2011
DOI: 10.1038/hdy.2011.31
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and genetic factors shaping contemporary metapopulation effective size and its empirical estimation in salmonid fish

Abstract: The preservation of biodiversity requires an understanding of the maintenance of its components, including genetic diversity. Effective population size determines the amount of genetic variance maintained in populations, but its estimation can be complex, especially when populations are interconnected in a metapopulation. Theory predicts that the effective size of a metapopulation (meta-N e ) can be decreased or increased by population subdivision, but little empirical work has evaluated these predictions. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 68 publications
3
28
0
Order By: Relevance
“…Recently, Palstra and Ruzzante (2011) found that the degree of connectivity in different salmon populations could be forecast from demographic and life history attributes. Species that are livebearers and mouth brooders, for example, are less likely to be constrained by larval dispersal because they tend to produce advanced offspring that are deposited into optimal habitats.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Recently, Palstra and Ruzzante (2011) found that the degree of connectivity in different salmon populations could be forecast from demographic and life history attributes. Species that are livebearers and mouth brooders, for example, are less likely to be constrained by larval dispersal because they tend to produce advanced offspring that are deposited into optimal habitats.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The resulting gene flow will contribute to the genetic constitution of the recipient population and affect the estimated N e. Difficulties in measuring N e also arise from the lack of adequately accounting for the spatial and metapopulation structure and clarity on how these affect N e . Depending on the variation in size and productivity of subpopulations and the patterns of migration and extinction/recolonization rates, the sum of N e 's of the subpopulations can either be greater or smaller than the effective size of the total (meta)population (N eT ) (Nunney 1999;Palstra and Ruzzante 2011). With high levels of dispersal, the concept of a (sub)population N e becomes increasingly meaningless since it is not acting as an independent unit (Nunney 2000).…”
mentioning
confidence: 99%
“…Palstra and Ruzzante (2011) urged further theoretical developments to avoid a downward bias in estimating linkage disequilibrium Ne in naturally occurring metapopulations. Our results have demonstrated that under certain circumstances even estimates for focal populations can be downwardly biased.…”
Section: Discussionmentioning
confidence: 99%
“…The samples would not represent a panmictic population, causing deviations from the expected linkage disequilibria and a bias in the linkage disequilibrium estimation of Ne . For example, a downward bias in Ne estimates was simulated by Palstra and Ruzzante (2011) when divergent populations were pooled.…”
mentioning
confidence: 99%